Ultrasound Assessment of Diaphragmatic Function: Methodology, Normative Values - P. G. Evgrafov; L. T. Khamidova; S. S. Petrikov (Неотложная медицинская помощь, 2025)
RELEVANCE. Diaphragmatic dysfunction (DD) is common in critically ill patients, and is often the cause of respiratory failure requiring respiratory support. A generally accepted method for noninvasive dynamic evaluation of diaphragm function has not yet been proposed.the AIM OF STUDY. To develop a method for ultrasound examination of diaphragm mobility and relative thickening, to propose standard parameters of diaphragm excursion and relative thickening depending on gender and age.MATERIAL AND METHODS. In 81 healthy volunteers aged 25 to 84 years (mean age 55±15 years), we used ultrasound to determine the thickness of the diaphragm on the right and left at the attachment site of the muscular part on end-expiration, tidal and forced inspiration; to calculate the fractional thickening (FT), diaphragm excursion during quiet and maximum inspiration, as well as indices of functional reserve by thickening (IFR(t)) and by diaphragm excursion (IFR(e)). We traced the dependence of the determined parameters on the age, gender, height, body mass index (BMI) and body surface area (BSA) of the subjects. To assess interobserver reproducibility, we calculated the limits of agreement and the intraclass correlation coefficient of the ultrasound parameters of the diaphragm function.RESULTS. The excursion of the diaphragm in women is smaller than in men, and statistically significantly decreases with age. A direct relationship between the thickness of the diaphragm on exhalation and the BSA was demonstrated. The FT during quiet inspiration on the left slightly but statistically significantly decreases with increasing BMI. The IFR(t) on the right slightly but statistically significantly decreases with age. The lower limits of the reference intervals for IFR(e) and IFR(t) do not depend on the factors considered and are the same for the right and left halves of the diaphragm. Inter-study reproducibility of ultrasound indices of diaphragm function is high: intra-class correlation coefficients for various parameters ranged from 0.81 to 0.96, measurement error according to the results of Bland-Altman analysis was small relative to the measured values.CONCLUSION. A method for ultrasound examination of diaphragm function is proposed. High inter-study reproducibility of the considered ultrasound parameters was confirmed, reference intervals were proposed. Functional reserve indices do not depend on age, gender and constitutional characteristics of the subjects.